(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Encontros Bibli Vol. 18, n. 37 (2013) Link de acesso ao número https://periodicos.ufsc.br/index.php/eb/issue/view/2019/showToc